Analisis Eksistensi Humas CRN TV sebagai Media Jurnalisme di Fakultas Ilmu Sosial UIN Sumatera Utara Medan - Ade Kurniawan; Yose Rizal Saragih (Jurnal Ilmu Sosial dan Ilmu Politik)
The importance of the journalistic function of CRN TV's Public Relations in providing accurate information and fostering two-way dialogue between institutions and the public, particularly within the educational environment, is the focus of this study. The aim of this research is to identify and evaluate PR strategies in leveraging digital technology to enhance organizational image and communication effectiveness. This study employs a qualitative approach using case study methodology, involving participatory observation, in-depth interviews, and document analysis. Data were analyzed using qualitative analysis techniques to identify relevant patterns, themes, and meanings. The theoretical framework underpinning this research is strategic communication and relationship management theory, which emphasizes the significance of PR strategies in building and maintaining positive relationships with the public through the use of digital media. The findings reveal that CRN TV's Public Relations successfully manages content, builds media relations, and utilizes digital platforms for information dissemination. Public engagement and crisis management are also integral components of their communication strategy, proving effective in creating a positive image and strengthening public relationships. The conclusion of this study is that CRN TV's Public Relations plays a crucial role in enhancing organizational image and communication effectiveness through effective PR strategies and the utilization of digital technology.